2005
DOI: 10.1103/physrevb.71.140509
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic proximity effect in perovskite superconductor/ferromagnet multilayers

Abstract: YBa2Cu3O7/La 2/3 Ca 1/3 MnO3 superconducting/ferromagnetic (SC/FM) multilayers have been studied by neutron reflectometry. Evidence for a characteristic difference between the structural and magnetic depth profiles is obtained from the occurrence of a structurally forbidden Bragg peak in the FM state. The comparison with simulated reflectivity curves allows us to identify two possible magnetization profiles: a sizable magnetic moment within the SC layer antiparallel to the one in the FM layer (inverse proximit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
144
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(154 citation statements)
references
References 23 publications
10
144
0
Order By: Relevance
“…As was the case in Ref. 25, it may still happen that different models lead to similar results and therefore cannot be distinguished. As shown below, this ambiguity might be overcome with reflectivity curves that extend up to larger q z values where the differences between the various models become more pronounced.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…As was the case in Ref. 25, it may still happen that different models lead to similar results and therefore cannot be distinguished. As shown below, this ambiguity might be overcome with reflectivity curves that extend up to larger q z values where the differences between the various models become more pronounced.…”
Section: Resultsmentioning
confidence: 91%
“…PNR measurements on SLs with equally thick YBCO and LCMO layers, for which the even order superlattice Bragg-peaks should be absent for symmetry reasons, showed that a 2nd order Bragg peak appears and gains considerable intensity below the FM transition, T Curie , of the LCMO layers 25 . This observation clearly showed that the depth profile of the magnetic potential has a lower local symmetry than the nuclear one.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of novel phenomena like spin triplet superconductivity [5][6][7][8], superconducting spin switch [9][10][11][12], and vortex pinning by magnetic domain wall interactions [13] have been reported in them. Besides, the T C modulation of the S-layer in the presence of F-layer, the contrasting magnetic nature of S/F interface and deep inside the F-layer has also interested the researchers [14,15]. The later has been investigated by techniques such as neutron reflectometry and XMCD [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the T C modulation of the S-layer in the presence of F-layer, the contrasting magnetic nature of S/F interface and deep inside the F-layer has also interested the researchers [14,15]. The later has been investigated by techniques such as neutron reflectometry and XMCD [14,15].…”
Section: Introductionmentioning
confidence: 99%